Marine spatial closures as a supplementary tool to reduce discards in bottom trawl fisheries: examples from southern European waters - Despoti, Smaragda (2021)
Discards is an important issue in fisheries around the world. the spatial management of discards has attracted interest as a potential tool for minimizing the unwanted catch. the aim of the present work was to identify areas with high quantities of bottom trawl discarded catch regarding species subjected to MCRS, in six areas of southern European waters (southern Portuguese waters, Catalan Sea, Ligurian and northern Tyrrhenian Seas, Strait of Sicily, eastern Ionian Sea, and Aegean Sea). Analyses were based on two types of data: (a) the undersized catch of species subjected to MCRS from bottom trawl surveys and (b) the actual discarded catch (including undersized and non-undersized individuals) of species subjected to MCRS from commercial bottom trawling. Geostatistical analysis techniques were applied to the first type of data and Generalized Additive Models using environmental variables were applied to the second one. Subsequently, areas that persistently presented high quantities of discarded catch (i.e., "iDC grounds") or undersized catch (i.e., "iUC grounds") were identified and mapped. the "iDC grounds"/"iUC grounds" were located either over the slope or within the continental shelf and over marine plateaus, largely depending on the main target species of each fishery. Next, the overlap of "iDC grounds"/"iUC grounds" with the existing Fisheries Restricted Areas (FRAs) and the proposed Marine Protected Areas (MPAs) was estimated aiming to explore how spatial closures could contribute to the reduction of bottom trawl discarded catch/undersized catch. Certain spatial closures were more effective in the Central Mediterranean and others to the Eastern Mediterranean. the overlapping of existing FRAs with "iDC grounds"/`iUC grounds" did not exceed 24 % in any study area, whereas proposed MPAs, like the CIESM Marine Peace Parks, reached up to 90 % for the same study area.